(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The analysis blockchain-based approaches for several analysis armed forces. These services include confirmation, discretion, privacy and admission control list (ACL), data and supply attribution, and reliability assurance. All these services are critical for the current distributed applications, especially due to the large amount of data being processed over the networks and the use of cloud computing. Validation ensures that the user is he/she claims to be. Discretion guarantees that facts cannot be read by unconstitutional users. Privacy provides the users the ability to control who can access their facts. Derivation allows a capable tracking of the facts and resources along with their rights and exploitation over the network. Reliability helps in verifying that the facts has not been tailored or misused. These services are currently managed by centralized controllers, for example, credential ability. Therefore, the services are lying on your front to attacks on the centralized director. On the other hand, blockchain is a secured and scattered ledger that can help resolve many of the problems with centralization. The objectives of this paper are to give insights on the use of protection services for current applications, to emphasize the state of the art techniques that are currently used to provide these services, to describe their challenges, and to discuss how the blockchain technology can resolve these challenges. Further, several blockchain-based approaches providing such protection services are compared thoroughly. Challenges associated with using blockchain-based security services are also discussed to prompt further research in this area